Nrf2 Pathway Regulates Multidrug-Resistance-Associated Protein 1 in Small Cell Lung Cancer - Ji, Lili; Li, Hui; Gao, Pan; Shang, Guoguo; Zhang, Donna D.; Zhang, Nong; Jiang, Tao (PLOS ONE, 2013)
Although multidrug-resistance-associated protein-1 (MRP1) is a major contributor to multi-drug resistance (MDR), the regulatory mechanism of Mrp1 still remains unclear. Nrf2 is a transcription factor that regulates cellular defense response through antioxidant response elements (AREs) in normal tissues. Recently, Nrf2 has emerged as an important contributor to chemo-resistance in tumor tissues. In the present study, the role of Nrf2-ARE pathway on regulation of Mrp1 was investigated. Compared with H69 lung cancer cells, H69AR cells with MDR showed significantly higher Nrf2-ARE pathway activity and expression of Mrp1 as well. When Nrf2 was knocked down in H69AR cells, MRP1's expression decreased accordingly. Moreover, those H69AR cells with reduced Nrf2 level restored sensitivity to chemo-drugs. To explore how Nrf2-ARE pathway regulates Mrp1, the promoter of Mrp1 gene was searched, and two putative AREs—ARE1 and ARE2—were found. Using reporter gene and ChIP assay, both ARE1 and ARE2 showed response to and interaction with Nrf2. In 40 cases of cancer tissues, the expression of Nrf2 and MRP1 was measured by immunohistochemistry (IHC). As the quantitive data of IHC indicated, both Nrf2 and MRP1 showed significantly higher expression in tumor tissue than adjacent non-tumor tissue. And more important, the correlation analysis of the two genes proved that their expression was correlative. Taken together, theses data suggested that Nrf2-ARE pathway is required for the regulatory expression of Mrp1 and implicated Nrf2 as a new therapeutic target for MDR.